Tinjauan Yuridis Penyembunyian Identitas Pelaku Tindak Pidana Dalam Acara Bertema Investigasi Kriminal - Rizqa Putri; Davit Rahmadan; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Hiding the identity of criminals by the press in events themed on criminal investigations is a case that must be examined and cannot be ignored, this is because it can harm the wider community. In investigating or seeking information, journalists always prioritize personal interests over public interests, this can be seen from, for example, the sale of fake cosmetics, the sale of dangerous food, with journalists receiving the information and not reporting to the authorities, therefore journalists are also included in article 165 of the Criminal Code. . Meanwhile, in Article 165 of the Criminal Code, journalists do not get exceptions. Therefore journalists have violated the article. Regarding the right to refuse for this case it does not apply because in Law no. 40 of 1999 the right to refuse can be canceled in the interest of the state. From the results of the study there are three main things that can be concluded. First, law enforcement against cases of concealing the identity of criminals by the press, which is a form of crime by knowing there is a crime but not by reporting it to judicial officials or the police. This has been stated in Article 165 of the Criminal Code. With this, the judiciary and the police must take firm action against the press so as not to harm the wider community. Second, the sanctions applied in accordance with the case of concealing the identity of the perpetrators of criminal acts by the press must comply with the provisions of Article 165 of the Criminal Code, in order to realize the justice desired by all communities. Author's suggestion, First, there is a need to revise Law no. 40 of 1999 concerning the Press in order to provide clearer certainty to members of the press. Second, there needs to be attention from the legal apparatus and the community so that the realization of forming a new law can be realized. Third, there needs to be a direct effort from the government to approve and handle several issues related to the press around the community.Keywords: Press- Criminal Investigation- Crime